PENERAPAN 3D PRINTING DALAM MENGEDUKASI SISWA SEJAK DINI PADA PEMBUATAN BENDA TIGA DIMENSI UNTUK SISWA SEKOLAH DI MUARA GEMBONG - Syaefudin, Eko Arif; Ahmad Kholil; Ragil Sukarno; Akhmad Saufan; Djoko Walujo; Muhammad Shafwan Muhadzdzib; Munjir Hakim (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract State Senior High School 1 in Muara Gembong District is around 45 km from Jakarta State University. The partner's current problem is that students still don't have the skills to make 3-dimensional models using technological means. The Vocational schools as schools to develop quality graduate have a vision of making their students superior and specialy in creativity to making 3-dimensional models. Currently, the introduction of making 3-dimensional models quickly has begun to be introduced students from an early age, especially in superior schools in big cities. Limited school facilities such as 3D printers will be a weakness for students in learning how to make and analysis design real in 3-dimensional models quickly. The module is made simply to learn and can be made 3D object model its simple easy by vocational high school students. The output of this activity program is learning modules/slides on making 3-Dimensional objects for vocational high school students, intellectual property rights, online media publications and articles. Abstrak SMAN 1 di Kecamatan Muara Gembong berada sekitar 45 km dari Universitas Negeri Jakarta. Permasalah mitra saat ini adalah Keterampilan siswa dalam pembuatan model 3 dimensi dengan sarana teknologi masih belum memiliki. Sekolah SMK sebagai sekolah kejuruan memiliki visi menjadikan siswanya unggul dan kreatif dalam pembuatan model 3 dimensi. Saat ini pengenalan pembuatan model 3 dimensi secara cepat sudah mulai dikenalkan kepada siswa dari semenjak dini terutama di sekolah unggulan di kota besar. Fasilitas Sekolah yang terbatas seperti sarana 3D printer ini akan menjadi kelemahan siswa dalam mempelajari bagaimana pembuatan model 3 dimensi secara cepat. Modul dibuat secara sederhana dan bisa dibuat oleh siswa SMK / SMA. Luaran program kegiatan ini adalah modul pembelajaran pembuatan 3 dimensi untuk siswa SMK / SMA, HKI, publikasi media online dan artikel.